2007
DOI: 10.1088/1475-7516/2007/06/009
|View full text |Cite
|
Sign up to set email alerts
|

A black-hole accretion disc as an analogue gravity model

Abstract: We formulate and solve the equations governing the transonic behaviour of a general relativistic black-hole accretion disc with non-zero advection velocity. We demonstrate that a relativistic Rankine-Hugoniot shock may form leading to the formation of accretion powered outflow. We show that the critical points of transonic discs generally do not coincide with the corresponding sonic points. The collection of such sonic points forms an axisymmetric hypersurface, generators of which are the acoustic null geodesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 83 publications
(157 reference statements)
1
83
0
Order By: Relevance
“…[14], and for recent applications to accretion flows on black hole backgrounds, see Refs. [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[14], and for recent applications to accretion flows on black hole backgrounds, see Refs. [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This will help in studying the low angular momentum pseudo-Schwarzschild axisymmetric black hole accretion as a natural example of analogue gravity phenomena. It has recently been shown that the analogue surface gravity can be computed for multi-critical accretion onto astrophysical black holes (Abraham et al 2006;Das et al 2007). The present work will allow to study such phenomena for various different geometric configuration of the flow.…”
Section: Discussionmentioning
confidence: 99%
“…Recent works Abraham et al [2006], Das et al [2007], Pu et al [2012] demonstrate the emergence of such acoustic geometry and corresponding multiple acoustic horizons -one white hole type and two black hole type -within the general relativistic accretion of matter onto astrophysical black holes, either of the Schwarzschild or of the Kerr type. In these works, however, only a particular type of flow geometry (either flow with constant disc thickness or flow in hydrostatic equilibrium along the vertical direction) has been considered to study such emergent gravity phenomena.…”
Section: Introductionmentioning
confidence: 99%